Reconstrucción de brazo afectado por tumor de células de Merkel, con colgajo gran dorsal pediculado. - BARDALES LASTEROS, Alberto (2013)
Latissimus dorsi flap is versatile to cover local defects as at distance. The tumor of cells of Merkel is not very frequent and it appears in exposed areas in the sun. Case Report: Patient female 55 years with tumoracion in left arm. Tumoracion is dried up and it is carried out reconstruction of the area with a ipsilateral. latissimus dorsi flap. Conclusion: The tumor of Merkel involves an extensive area of the left arm, creating a great defect in the resection. Latissimus dorsi flap contributes muscular and cutaneous to cover the great and deep defects. for the reconstruction.